JAPAN’S ECONOMIC SITUATION OVER THE LAST 10 YEARS - Ulug‘murodov F.F; Jamilov F.O (TADQIQOTLAR, 2026)
Abstract. This article is devoted to analyzing the development of Japan’s economy in recent years under conditions of global economic changes. The study assesses post-pandemic recovery processes as well as the main directions of economic and fiscal policy. The analysis is based on statistical data and macroeconomic indicators. The results show that Japan’s economy has prospects for sustainable growth up to 2030, with significant opportunities particularly in the fields of technological development and green energy. The findings of the study are of practical importance for shaping economic policy and directing investments toward priority areas.